THE INFLUENCE OF INTELLECTUAL CAPITAL, GOVERNANCE AND ORGANIZATIONAL CULTURE ON COMPANY PERFORMANCE - Yulaeli, Tri (2021)
The focus of this research was to ascertain the effect of intellectual capital, corporate governance, and organizational culture on the performance of manufacturing companies listed on the IDX from 2018 to 2020. This study is conducted quantitatively. The population for this study is all manufacturing firms that are publicly traded on the Indonesian Stock Exchange (IDX). Meanwhile, the sample selection from this research used the purposive sampling method and was selected based on certain criteria and totaled 278 companies. The types of data in this study are primary and secondary data collected using the method of observation and literature study. Data analysis in this study uses several analytical methods, namely Normality Test, Model Testing (simple correlation coefficient matrix), and Hypothesis Testing. Based on the results of data analysis, it can be concluded that: 1) Intellectual Capital has a positive and significant effect on company performance with a C.R. (critical ratio) value of 3.844 > 1.96 and a P value of 0.000 < 0.15; 2) Good Corporate Governance has a positive and significant impact on company performance with a C.R. (critical ratio) value of 2.291 > 1.96 and a P value of 0.000 < 0.23; and 3) Organizational Culture has a positive and significant effect on company performance with a C.R. (critical ratio) value of 3,019 > 1.96 and a P value of 0.003 < 0.23.